2022
DOI: 10.21203/rs.3.rs-1331186/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optical stimulation of inferior temporal cortex induces object-specific visual distortions.

Abstract: To be able to effectively restore vision by direct cortical stimulation, we need to understand the perceptual events induced by stimulation of high-level visual cortices. We trained macaque monkeys to detect and report optogenetic impulses delivered to their inferior temporal cortices. In a series of experiments, we observed that detection of cortical stimulation highly depends on the choice of images presented to the eyes and that detection of cortical stimulation is most difficult when the animal fixates on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…It has been previously shown that monkeys can easily learn this simple task (14,15), which remained the sole task expected from the animals throughout the study. Our earlier results suggest that the animals perform this task (in the IT cortex) using the visual events induced by cortical stimulation (6). The animals initiated each trial by holding fixation on a central target for 500ms.…”
Section: Perceptography: Concept and Methodologymentioning
confidence: 95%
See 4 more Smart Citations
“…It has been previously shown that monkeys can easily learn this simple task (14,15), which remained the sole task expected from the animals throughout the study. Our earlier results suggest that the animals perform this task (in the IT cortex) using the visual events induced by cortical stimulation (6). The animals initiated each trial by holding fixation on a central target for 500ms.…”
Section: Perceptography: Concept and Methodologymentioning
confidence: 95%
“…The Opto-Array allows safe, rapidly reversible, and high-throughput optical stimulation of ∼1mm3 subregions of the targeted cortex, although it doesn’t allow neural recordings. Technical details about the Opto-Array and relevant surgical protocols can be found in our earlier reports ( 2, 6 ).…”
Section: Perceptography: Concept and Methodologymentioning
confidence: 99%
See 3 more Smart Citations